2019
DOI: 10.1080/00016489.2019.1657240
|View full text |Cite
|
Sign up to set email alerts
|

Current state of evidence for endolymphatic sac surgery in Menière’s disease: a systematic review

Abstract: Terms of use This work is brought to you by the University of Southern Denmark through the SDU Research Portal. Unless otherwise specified it has been shared according to the terms for self-archiving. If no other license is stated, these terms apply: • You may download this work for personal use only. • You may not further distribute the material or use it for any profit-making activity or commercial gain • You may freely distribute the URL identifying this open access version If you believe that this document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Currently, the most popular surgical procedures to control vertigo attacks in MD are also the most aggressive and those that have the most negative impact on auditory function. Besides, there is a lack of evidence suggesting that surgical therapy for MD may provide a significant control of symptoms 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the most popular surgical procedures to control vertigo attacks in MD are also the most aggressive and those that have the most negative impact on auditory function. Besides, there is a lack of evidence suggesting that surgical therapy for MD may provide a significant control of symptoms 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most popular surgical procedures to control vertigo attacks in MD are also the most aggressive and those that have the most negative impact on auditory function. Besides, there is a lack of evidence suggesting that surgical therapy for MD may provide a significant control of symptoms 35 . The table below shows the main surgical procedures for MD taking into account of hearing preservation, vestibular injury, surgical difficulty and long-term outcomes (Table 1).…”
Section: Surgical Innovationsmentioning
confidence: 99%
“…Since then, practically, all animal research and clinical treatments, including popular endolymphatic shunt surgery, were based on this concept. Recent studies, including clinical blind studies, have shown that Meniere's disease should not be based on the endolymphatic hydrops theory (Thomsen et al, 1981a , b , 1998 ; Bretlau et al, 1984 ; Merchant et al, 2005 ; Devantier et al, 2019 ). Unfortunately, because of the postulated incorrect etiology, decades of research became useless, and many patients underwent serious operations which were not better than placebo.…”
Section: Current Status In the Field Of Misophoniamentioning
confidence: 99%
“…The methodology used in the Danish Health Authority guideline development has previously been described [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. In short, the methodology is based on the recommendations for conducting systematic reviews and meta-analyses from the Cochrane Handbook for systematic reviews [ 8 ].…”
Section: Introductionmentioning
confidence: 99%